A guide to Oracle including Developer/2000 and the Oracle WebServer and DBA utilities - Morrison, Joline; Morrison, Mike (Course Technnology, 1998)
This text provides comprehensive instruction that should enable students to develop a database in Oracle, using the database and application development tools provided by the Oracle Academic Alliance Program.